A very rare side effect of mitomycin-C: psoriasiform drug eruption - Cicek, Demet; Cobanoglu, Bengu; Inci, Rahime; Dertlioglu, Selma Bakar; Kokcam, Ibrahim; Elkiran, Tamer (Wiley-Blackwell, 2013)
[Abstract Not Available]